Corrosion Inhibition and Adsorption Characteristics of Tarivid on Mild Steel in H2SO4 - N. O. Eddy; E. E. Ebenso (E-Journal of Chemistry)
The corrosion inhibition and adsorption characteristics of (+/-)-9-fluoro-2,3-dihydro-3-methyl-10-(4-methyl-1-piperazinyl)-7-oxo-7H-pyrido[1,2,3-de]-1,4-benzoxazine-6-carboxylic acid (Tarivid) on the corrosion of mild steel has been studied using thermometric and gasometric methods. The study reveals that tarivid inhibits the corrosion of mild steel in H2SO4. The values of inhibition efficiency of tarivid were found to increase as its concentration increased but decreased with increase in temperature. Activation energies of the inhibited corrosion of mild steel ranged from 39.05 to 50.61 kJ/mol. Values of enthalpy change and free energy of adsorption were negative which indicated exothermic and spontaneous adsorption process. Physical adsorption mechanism is proposed from the obtained kinetic and thermodynamic parameters. Langmuir adsorption isotherm model is obeyed from the fit of the experimental data.